Cranberry extract for symptoms of acute, uncomplicated urinary tract infection - Gbinigie, OA (2021)
Background There is growing interest in using non-antibiotic treatments for common bacterial infections, such as Urinary Tract Infections (UTI). One potential non-antibiotic treatment for acute uncomplicated UTI is cranberry extract.